2018
DOI: 10.3389/fpsyg.2018.00446
|View full text |Cite
|
Sign up to set email alerts
|

Children Facial Expression Production: Influence of Age, Gender, Emotion Subtype, Elicitation Condition and Culture

Abstract: The production of facial expressions (FEs) is an important skill that allows children to share and adapt emotions with their relatives and peers during social interactions. These skills are impaired in children with Autism Spectrum Disorder. However, the way in which typical children develop and master their production of FEs has still not been clearly assessed. This study aimed to explore factors that could influence the production of FEs in childhood such as age, gender, emotion subtype (sadness, anger, joy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…cross-cultural studies indicate that the intensity of spontaneous expression is not universal and may vary across cultures) [10,11]. Similarly, in a previous study [6], we found that children from the south of France (Nice) were more expressive than children from the north (Paris).…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…cross-cultural studies indicate that the intensity of spontaneous expression is not universal and may vary across cultures) [10,11]. Similarly, in a previous study [6], we found that children from the south of France (Nice) were more expressive than children from the north (Paris).…”
Section: Introductionsupporting
confidence: 84%
“…The protocol is available in detail in Grossard et al [6]. It consists of two tasks of FE production, one entailing a verbal request without a model (the on request task) and one entailing the imitation of an avatar (the imitation task).…”
Section: Tasksmentioning
confidence: 99%
See 3 more Smart Citations